Web-Based Academic Potential Test Information System (Case Study: Faculty of Teacher Training and Education Victory University of Sorong) - Natasya V. Leuwol; Melda Agnes Manuhutu; Muhammad Z. Sirajuddin (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
Academic Potential Test (TPA) is a test used to measure a person's ability level. At the Faculty of Teacher Training and Education (FKIP) Victory University, Sorong, TPA was held before the Field Experience Program (PPL) where the implementation was still manual, namely the test was carried out in writing using paper and corrections by the lecturer. It takes a long time to correct and uses a lot of paper. The purpose of this research is to design a Web-Based Academic Potential Test Information System. System development used the prototype method. This research used the PHP programming language, the database is built using MySQL. The result of this study is that this web-based academic potential test information system helps FKIP in conducting online academic potential tests, where this test can be taken anywhere and can see the results directly after taking the test